2021
DOI: 10.3389/fenrg.2021.701901
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Alternative Jet Fuel Dependencies Between Combustors of Different Size and Mixing Approaches

Abstract: Analyses used to reveal fuel dependencies on lean blow out and ignition at specific operating conditions in specific combustors show inconsistent trends with each other. Such variety is however consistent with the occurrence of transitions between the governing physical phenomena as the ratios between evaporation, mixing, or chemical time scales with their respective residence times also vary with specific operating conditions and combustor geometry. It is demonstrated here that the fuel dependencies on LBO in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In the same program, similar trends were observed during the LBO-limit and ignition tests performed on lab-scale and proprietary combustors. Data analysis by Boehm et al [84] suggested LBO figures of merit to be remarkably influenced by 20% recovered temperature (T 20 ) and density, selected as representative independent variables of evaporation and atomization, respectively. In addition, it was shown that some fuel dependencies emerge over a wide range of combustor length scales and design approaches, and similar trends can be identified for two systems operated at conditions that match ratios of characteristic timescales (e.g., evaporation-to-residence-time).…”
Section: Outlook On Fuel Effects In Aviation Researchmentioning
confidence: 99%
“…In the same program, similar trends were observed during the LBO-limit and ignition tests performed on lab-scale and proprietary combustors. Data analysis by Boehm et al [84] suggested LBO figures of merit to be remarkably influenced by 20% recovered temperature (T 20 ) and density, selected as representative independent variables of evaporation and atomization, respectively. In addition, it was shown that some fuel dependencies emerge over a wide range of combustor length scales and design approaches, and similar trends can be identified for two systems operated at conditions that match ratios of characteristic timescales (e.g., evaporation-to-residence-time).…”
Section: Outlook On Fuel Effects In Aviation Researchmentioning
confidence: 99%
“…Although jet fuel combustion has been studied for decades, unknowns remain. For example, critical factors for altitude relight are not well characterized: atomization is a complex interplay of fuel surface tension, viscosity, density, and air temperature and pressure; fuel vapor pressure, and molecular composition are also important (Peiffer et al, 2019;Boehm et al, 2021). Research, such as the National Jet Fuels Combustion Program (Colket et al, 2016;CAAFI R&D Team, 2019), has added to the understanding of the interaction of fuel chemical composition and physical properties with combustion.…”
Section: Importance Of "Drop-in" As a Requirementmentioning
confidence: 99%
“…For 100% synthesized fuels, new requirements may need to be added to the specification. For example, the NJFCP suggested several characteristics as potentially critical to the safety and operability of jet fuels, such as derived cetane number (Colket et al, 2016;Stachler et al, 2020;Boehm et al, 2021). These new requirements need to be considered, researched and verified.…”
Section: Importance Of "Drop-in" As a Requirementmentioning
confidence: 99%